Low Carbohydrate Beers Produced by a Selected Yeast Strain from an Alternative Source. (2nd January 2020) - Troilo, Antonio; De Francesco, Giovanni; Marconi, Ombretta; Sileoni, Valeria; Turchetti, Benedetta; Perretti, Giuseppe
Abstract: Recently, the brewing industry has invested significant resources into the development of new specialty beers, in response to increased consumer demand. Low carbohydrate and novel flavored beers have resulted and these are particularly attractive for consumers, even if technologically challenging to produce. The aim of this work was to produce a low carbohydrate and novel flavored beer in a traditional manner. A Saccharomyces cerevisiae strain isolated from an alternative source (i.e., yeast strain DBVPG 6580 was used in a Brazilian bioethanol production facility) was selected because of its starch degrading character and this yeast was employed in a traditional brewery plant to achieve this goal. The strain DBVPG 6580 was used to ferment worts of different densities (12 and 20°P) and at different fermentation temperatures (18 and 25 °C), to explore possible technological applications. The results demonstrated that yeast DBVPG 6580 was able to degrade dextrins to fermentable sugars, giving an apparent attenuation above 100% and allowing for the production of a low carbohydrate beer by traditional methods. Moreover, strain DBVPG 6580 produced novel flavored beers, rich in fruity, floral, banana and pear flavors. This yeast strain demonstrated that under optimal conditions, it possessed the ability to ferment a high density wort, which could lead to important economic advantages for the producer.